The economics of precision guidance with auto-boom control for farmer-owned agricultural sprayers - Batte, Marvin T.; Ehsani, Mohammad Reza (Computers and electronics in agriculture, 2006)
Precision guidance and precision sprayer control have substantial promise to reduce input application overlap, thus saving chemicals, fuel, and time during the application process. In this article we provide preliminary estimates of the magnitude of the private benefits for a precision guidance system combined with auto-boom control for agricultural sprayers (precision spraying). Hypothetical farm fields are analyzed, allowing comparison of the performance of the precision system to a traditional, non-precision system for different field shapes. An analysis of the impact of size of farm on system profitability also is explored. Our analyses suggest that, even when considering only private benefits of input savings, the value derived from a precision spraying system can be substantial. This is especially true when the sprayer patterns become more complex due to non-rectangular fields and due to the presence of waterways, drainage ditches or similar obstructions. Economic benefits of the precision spraying system increase proportionally to the cost of the spray material being applied and with the number of annual applications. Benefits also increase with increases in driver error rates for non-precision systems. Because most of the costs of the precision spraying system relate to the fixed investment, these costs are largely constant regardless of farm size. This translates to net benefits of precision spraying that increase with increased farm size.